OTA-based voltage-mode universal biquadratic filter with single-input multiple-output - Kumngern, Montree; Junnapiya, Somyot (My University, 2012)
This paper presents an electronically tunable voltagemode universal biquadratic filter with single input and five outputs employing six operational transconductance amplifiers, two grounded capacitors and one resistor. The proposed circuit can realize voltage-mode low-pass, band-pass, high-pass, bandstop and all-pass filter responses without inverting-type input signal requirements. The natural frequency and the quality factor can be orthogonally controlled. Also the natural frequency can be electronically tuned. The active and passive sensitivities of the circuit are low. PSPICE simulation results are provided to demonstrate the theoretical analysis. © 2012 IEEE.
Keywords: Analog signal processing; Biquad filter; Operational transconductance amplifier; Voltage-mode circuit